The Muslim Brotherhood, its youth, and implications for U.S. engagement - Martini, Jeffrey; Kaye, Dalia Dassa; York, Erin (Rand Corporation monograph series., 2012)
"Since the January 25 Revolution of 2011 that ousted Hosni Mubarak, the Muslim Brotherhood (MB) has emerged as a legal entity operating the Freedom and Justice Party (FJP). That party won a strong plurality in the 2011-2012 parliamentary elections as well as claiming the presidency. But while the group was one of the primary beneficiaries of the revolution, its future is clouded by serious generational divides within the organization. The MB is led by an aged leadership whose formative experience was the mihna (ordeal) of the 1960's when the state tried to stamp out the Islamist movement. This hardened the group's leaders and put a premium on secrecy and organizational security. Although individuals under the age of 35 make up a large share of the MB's membership, their participation is modeled on the principle of "listen and obey." This overbearing hierarchy has already led to splits within the MB and will continue to present challenges going forward. These youth merit attention not only as a challenge to the Brotherhood's organizational cohesion, but also as a potential conduit for expanding U.S. engagement with the group. This study presents several recommendations on how the United States can incorporate MB youth into engagement efforts, including understanding but not gaming divisions in the organization, expanding engagement beyond a handful of MB senior leaders, leveraging existing outreach programs to include MB youth, and cultivating leadership buy-in for youth engagement efforts."